Early Cinema, Modernity and Visual Culture : The Imaginary of the Balkans - Grgić, Ana (Eastern European screen cultures., 2022)
The end of the nineteenth century saw the Balkans animated with cultural movements and socio-political turmoil. Alongside these developments, the proliferation of print media and the arrival of moving images was transforming urban life and played a significant role in the creation of national culture. Based on archival research and previously overlooked footage and early press materials. Imaginary of the Balkans: Visual Culture, Modernity and Early Cinema is the first study on early cinema in the region from a transnational and cross-cultural perspective. This work investigates how the unique geopolitical positioning of the Balkan space and the multi-cultural identity of its communities influenced and shaped visual culture and early cinema development. Moreover, it examines the relationship between the new medium and visual culture through the notion of the haptic, and explores the role early cinema and foreign productions played in the construction of Balkanist and semi-colonial discourses. Reframing hierarchical relations between centres and peripheries, this book departs from approaches such as new cinema history and vernacular modernity to counter modernity discourses of lacks and absences, and instead, establishes new connections between moving image and print artefacts, early film practitioners and intellectuals, the socio-cultural context and cultural responses to the new visual medium. Ana Grgi is Assoc. Professor at Babes-Bolyai University. Her research on Balkan and transnational cinema, archives and memory appeared in Early Popular Visual Culture, Studies in Eastern European Cinema, Film Quarterly, and KinoKultura. She is co-editor of Contemporary Balkan Cinema: Transnational Exchanges and Global Circuits (2020), and is Associate Editor of Studies in World Cinema.